Karakteristik Ekstrak Pewarna Alami Daun Singkong (Manihot esculenta) pada Perlakuan Jenis Pelarut dan Suhu Maserasi - Hutabarat, Rian Lamhot Parasian; Wartini, Ni Made; Antara, Nyoman Semadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
This study aims to determine the effect of type of solvent and maceration temperature on the characteristics of cassava leaves extracts as a natural dyes leaves and determine the type of solvent for cassava leaf powder and the best maceration temperature to obtain the extract of natural cassava leaves. This study used a factorial randomized block design with 2 factors, namely the type of solvent (85% ethanol, 85% acetone and mixture (85% ethanol: 85% acetone) and maceration temperature (35 ° C, 45 ° C and 55 ° C). The data obtained were analyzed with variance and if the treatment had a significant effect, then continued with the Tukey test. The results showed that the treatment interactions had a very significant effect on yield, chlorophyll b, brightness (L *), yellowish level (b *), total chlorophyll, chlorophyll a. , redness (a *), but had no significant effect on the interaction at the level of redness (a *). The treatment of 85% acetone solvent and 55 ° C maceration temperature was the best treatment to produce acetone extract of natural dye of cassava leaves with yield characteristics of 14, 04%, total chlorophyll 12.10%, chlorophyll a 4.39%, chlorophyll b 7.71%, brightness (L *) 16.46, redness (a *) 9.77 yellowish (b *) of 5.70.brightness level (L*) of 11.03, redness level (a*) of 10.29, yellowish level (b*) of 2.83. Key words : cassava leaves, dye extract, maceration temperature, natural dye, solvent type .